DEVELOPING INTERACTIVE MULTIMEDIA FOR TEACHING READING SKILL NARRATIVE TEXT FOR NINTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Daryusman, Karsa; Susilawati, Endang; Rahmani, Eka Fajar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to develop interactive multimedia as a teaching and learning media to teach reading narrative text to the ninth-grade student"™s SMP negeri 4 Sambas. The form of this research was Research and Development (RD). This RD research was conducted to produce innovative teaching media. The method of this research was adapted from Branch (2009), that consists of three phases namely analyzing, designing, and developing (ADD). In the analyze phase found that the actual conditions of students and the teacher. Design phase was done to prepare the appropriate material to create the application. Develop phase was done to create an essential part of the Interactive multimedia using software called Smart App Creator (SAC). The designed product was completed after having internal validation regarding to the needs. As a result, Interactive multimedia is useable to support the process of teaching and learning reading narrative text for the nineth-grade student"™s SMP Negeri 4 Sambas.      Copyright © 2022 Karsa Daryusman, Endang Susilawati, Eka FajarRahmani.